Produção de recobrimentos resistentes ao desgaste através de laser cladding de pós das ligas amorfizáveis fe-co-nb-b-(y) - Lucena, Felipe Amélio de (Universidade Federal de São Carlos, 2020)
Industrial components can be subjected to a high level of surface wear it necessary to search for new wear-resistant alloys to improve the performance and safety of the components. The objective of this work was to produce laser coatings with high hardness and high wear resistance. Three new vitreous alloys of the Fe-Co-Nb-B-Y system were produced in the arc furnace integrated with the suction system using commercial raw materials (Fe-Nb and Fe-B ferroalloys). Subsequently, through the high energy milling process of the splat plates (> 10 cm) generated during gas atomization, powders (∅ <45 μm) were formed for Fe66Co7Nb4B23 and Fe63Co7Nb4B23Y3 (% at.) alloys. Three different coatings (B, C and D) were produced using the Fe66Co7Nb4B23Y3 (% at.) alloy and one coating (A) for the Fe66Co7Nb4B23 (% at.) alloy for comparison. Each coating was produced using different laser parameters and the powders from the milling. The coatings were subjected to the wear test of pin on disk and Vickers hardness. The “A” coating showed a lower average value of the specific wear rate (2.20 x10-5 mm3/Nm) and a higher average value of the friction coefficient (≈ 1.15) compared to “B” coating. The laser remelting process applied over “C” coating and the addition of a second coating layer in the formation of “D” coating did not significantly change its specific wear rates, which were similar in “B” coating (10.9 x 10-5 mm3/Nm). The friction coefficient of “B” coating (≈ 0.5) increased to ≈ 0.7 after its laser remelting for the formation of “C” coating and decreased to ≈ 0.35 in “D” coating with the addition of a second coating layer. The laser cladding process allowed the production of coatings with high hardness (575 ± 60 to 1160 ± 80 HV).
Production of wear resistance coating by laser cladding using glassy powders of fe-co-nb-b-(y) alloy system
Keywords: Liga vítrea à base de Fe; Pós atomizados; Laser cladding; Microdureza; Desgaste; Fe-based bulk metallic glasses; Coating; Wear; Pin on disk; Microhardness; Supercooled liquid; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA